Proposed Marketing Strategy For Arthetiks - Legia, Mariska; Aldianto, Leo (The Indonesian Journal of Business Administration, 2016)
Abstract. E-commerce is one of the fastest growing fields of business globally. This phenomenon leads to the shift of products and services distribution that include its promotion through Social Networking Sites, including Arthetiks. Through this circumstance, Arthetiks, a homegrown brand that focuses in producing travel mate for young and dynamic urbanites, needs to be able to keep up with the advancement, while taking advantage on the phenomenon at its best. Despite the usability and opportunity on technology advancement, yet the sales made were unsatisfying. The study conducted was the exploration on analyzation of the company’s external analysis through Porter’s Five Forces, and internal analysis that consists of the review of 7P’s Marketing Mix model and SWOT analysis to find the gaps and problems that led to the problems arose. The high unsatisfying results were the results from various causes, such as low customer satisfaction, lack of product differences, unorganized marketing activities and high rivalry.  Arthetiks needs to improve its marketing strategy and implement business derived strategic planning to strengthen its products identity and achieving its’ objectives. STP analysis is applied to help Arthetiks to optimize its’ marketing strategies, especially to effectively delivered the promotional strategies and to produce demands products of the target market. In addition, a new 7P’s Marketing Mix strategies needs to be proposed e.g. increasing product varieties and uniqueness,creating a user friendly website, contribute on collaborations, creating company Mobile App, placing the products on more consignment stores, also enhance promotion strategies, especially via cyber space. Hence, the implementation plan is crucial to ensure the solutions to be realized properly while avoiding any errors on new strategies implementation. It also consists of human resource and budgeting plan. In order to make measurable progress within its scope, budget and time manners, it must be detailed on a time-framed table. The phases’s procedures of the implementation plan are discussed for Arthetiks to meet its objective. Keywords: Social Media, Sales, STP, Marketing Mix